Peningkatan Kapasitas Kelompok Tani Sinar Bahagia dalam Diversifikasi Produk Kakao Dengan Penerapan Teknologi Berbasis Green Processing di Desa Bebidas - Yasa, I Wayan Sweca; Saloko, Satrijo; Dila, Baiq Fitriana; Fikriana, Garin; Muttalib, Surya Abdul (Jurnal Gema Ngabdi, 2025)
The capacity-building program for the Sinar Bahagia Farmers’ Group in Bebidas Village was implemented to strengthen farmers’ ability to diversify cocoa-based products through the application of green processing technologies. This community engagement initiative aimed to enhance postharvest efficiency, product quality, and economic value addition by utilizing environmentally friendly technologies such as solar dryers with photovoltaic panels, low-energy closed fermentation systems, and composting using EM4-enriched water. The methods employed included participatory training, technology demonstrations, production mentoring, and performance evaluation through measurements of cocoa bean quality, compost yield, and value-added analysis. The results indicated an increase in farmers’ knowledge from 54% to 88%, improved fermentation uniformity up to 85%, reduced drying time from 5–7 days to 2–3 days, and an increase in compost yield from 5.6% to 18.2%. Product diversification into organic cocoa powder, artisan chocolate, and pectin contributed to income growth of 18–72% for the group. Moreover, the program strengthened institutional capacity, enhanced women’s participation, and established a circular-economy-oriented farming model. In conclusion, the application of green processing effectively improved farmers’ capacities while expanding a sustainable cocoa value chain, and the program carries strong potential for replication in other cocoa-producing regions.